2021
DOI: 10.3389/fnut.2021.668622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Almond Consumption on Metabolic Risk Factors—Glucose Metabolism, Hyperinsulinemia, Selected Markers of Inflammation: A Randomized Controlled Trial in Adolescents and Young Adults

Abstract: A large percentage of the Indian population has diabetes or is at risk of pre-diabetes. Almond consumption has shown benefits on cardiometabolic risk factors in adults. This study explored the effect of almond consumption on determinants of metabolic dysfunction—blood glucose, lipids, insulin and selected inflammatory markers in adolescents and young adults aged 16–25 years from Mumbai city. This randomized controlled trial was conducted for a period of 90 days on individuals with impaired levels of fasting gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 46 publications
(34 reference statements)
0
40
0
2
Order By: Relevance
“…Finally, 24 RCTs consist of 31 arms were included in our meta-analysis (Abazarfard, Salehi, & Keshavarzi, 2014;C. E. Berryman, West, Fleming, Bordi, & Kris-Etherton, 2015;Bowen et al, 2019;Chen et al, 2017a;Coates et al, 2020;Cohen & Johnston, 2011;Damasceno et al, 2011;de Souza, Gomes, de Castro, & Mota, 2018;Dhillon, Tan, & Mattes, 2016;Dhillon et al, 2018;Dikariyanto et al, 2020Dikariyanto et al, , 2020Hou et al, 2018;Jenkins et al, 2008;Jung, Chen, Blumberg, & Kwak, 2018;Kalgaonkar et al, 2011;Lee et al, 2017;Li et al, 2011;Madan et al, 2021;Richmond, Williams, Mann, Brown, & Chisholm, 2012;Sabaté, Haddad, Tanzman, Li et al, 2011;Madan et al, 2021;Richmond et al, 2012;Sabaté et al, 2003;Tan & Mattes, 2013;M. Wien et al, 2010;M.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 24 RCTs consist of 31 arms were included in our meta-analysis (Abazarfard, Salehi, & Keshavarzi, 2014;C. E. Berryman, West, Fleming, Bordi, & Kris-Etherton, 2015;Bowen et al, 2019;Chen et al, 2017a;Coates et al, 2020;Cohen & Johnston, 2011;Damasceno et al, 2011;de Souza, Gomes, de Castro, & Mota, 2018;Dhillon, Tan, & Mattes, 2016;Dhillon et al, 2018;Dikariyanto et al, 2020Dikariyanto et al, , 2020Hou et al, 2018;Jenkins et al, 2008;Jung, Chen, Blumberg, & Kwak, 2018;Kalgaonkar et al, 2011;Lee et al, 2017;Li et al, 2011;Madan et al, 2021;Richmond, Williams, Mann, Brown, & Chisholm, 2012;Sabaté, Haddad, Tanzman, Li et al, 2011;Madan et al, 2021;Richmond et al, 2012;Sabaté et al, 2003;Tan & Mattes, 2013;M. Wien et al, 2010;M.…”
Section: Study Selectionmentioning
confidence: 99%
“…Wien et al, 2010;M. Wien et al, 2003), nine studies reported HbA1C (Bowen et al, 2019;Chen et al, 2017a;Cohen & Johnston, 2011;de Souza et al, 2018;Hou et al, 2018;Kalgaonkar et al, 2011;Madan et al, 2021;Richmond et al, 2012;M. Wien et al, 2010), 16 studies with 22 arms reported insulin (Bowen et al, 2019;Chen et al, 2017a;Coates et al, 2020; Records identified through database searching: PubMed, Scopus, ISI web of science, the Cochrane Library (n = 2,071)…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations